Prevalence Unintended Pregnancy and its Related Factors Among Currently Pregnant Women in Kangavar City (West Iran) - Saeedeh Shahbazin; Azadeh Gholamy (Shahid Sadoughi University of Medical Sciences, 2015)
Background: Unintended or unplanned pregnancy has been a distressing reality among females in the reproductive age group particularly in developing countries. The current study aimed to determine the prevalence of unintended pregnancy among married women in an urban community in Kangavar city state, to determine the associated factors of unintended pregnancy and to verify the reasons behind unintended pregnancy as perceived by the married women in the area. Materials and Methods: This study was carried out on 248 mothers who referred to health centers of Kangavar, and they were selected randomly. Data was collected by valid and reliable questionnaire. Results were analyzed in spss17. Results: The prevalence of unwanted pregnancy was estimated to be 21/2 percent .About 21.2 of women stated that their pregnancy was unplanned, two fifth of these mothers mentioned that their pregnancy was mistimed and the other three-fifth reported that they had Unwanted. There was a significant relationship between age and type of pregnancy (p<0.001), contraception methods and unintended pregnancy (p<0.001). Also results showed that there was a significant between age of women and kind of contraception methods, which they had used (p<0.001). Conclusion: It can be concluded that age and contraception methods have main effect on unintended pregnancy. So that by increasing the awareness of women about these methods can reduce the occurrence of this type of pregnancy.